Increased Physical Activity Decreases Prevalence of Periodontitis: The Korean National Health and Nutrition Examination Survey (KNHANES Ⅵ) (2013-2015) - Eun-Jeong KIM; Gyeong-Soon HAN (Tehran University of Medical Sciences, 2020)
No Abstract